ANALISIS PENGARUH VARIASI TEMPERATUR BAJA AISI 1018 TERHADAP KEKERASAN DENGAN METODE JOMINY TEST - Harjuma Harjuma; Simon Parekke (Jurusan Teknik Mesin, Universitas Halu Oleo, 2019)
Hardenability of steel is an important guide to determine the pattern of heat behavior and the nature of the material to be heat-treated in the production of components. One way to determine steel hardenability is by using Jominy test method. This study aims to determine the hardness of the AISI 1018 steel by varying temperature in heat treatment. Hardness test was conducted using the Rockwell method (HRA) by varying the heating temperature to 700 °C, 800 °C and 900 °C. The material used was AISI 1018 steel and water as a cooling medium. The standard for making specimens refers to the ASTM A 255 Jominy Test with the following dimension: length of specimen 101.6 mm x diameter of specimen 25.4 mm. Electric heating furnace was used to heat the specimen according to the desired temperature. After a 15-minute holding time, the specimen was then cooled in clean water as cooling medium using Jominy test apparatus. Each specimen was cooled by spraying clean water onto it for 10 minutes. The results showed that the maximum hardness value occurred at the end of the specimen closest to the center of the spray and that the hardness decreased as the distance from the tip of the specimen increased. The results also showed that the higher the given heating temperature, the higher the hardness value of the specimens. However, the increase in temperature does not have a significant effect. This was probably the result of improper selection of materials where the heat treatment requires that the specimen contains more than 0,3% carbon. The specimen was too long on the air when released from the furnace. Hardness of test results obtained at temperature at a heating temperature of 700 ° C the average hardness value was 48.72 kg / mm2, at a temperature heating of 800 ° C the average hardness value was 47.44 kg / mm2 and at a heating temperature of 900 ° C the average hardness value was 48.12 kg/mm2.